Narrative Writing Ability Performed by Students of Islamic High School Al Ukhuwah Sukoharjo: A Second Language Acquisition Case - Lukluk Khuurun Ain (Jurnal Bahasa, Sastra, dan Studi Amerika, 2023)
The research conducted at MA Al Ukhuwah Sukoharjo aimed to explore second language acquisition among high school students, specifically focusing on error types and factors influencing these errors with a gender-based analysis. Utilizing a descriptive qualitative approach and the four stages of analysis—domain, taxonomic, componential, and cultural theme—the study identified 841 errors, with misformation errors comprising the majority at 51.6%. Female students exhibited a higher error rate at 80.38% compared to their male counterparts (19.62%). Causes of errors, such as overgeneralization, incomplete rule application, incorrect hypothesis conception, and ignorance of rule restrictions, were identified, with the latter significantly impacting language mastery. These findings provide valuable insights for educators, informing strategies to address challenges in mastering English, particularly in areas like tense usage, sentence structure, diction, and conjunctions among high school students at MA Al Ukhuwah Sukoharjo.